Pregnancy in older women: Analysis of outcomes in pregnancies from donor oocyte In- vitro fertilization - James A Osaikhuwuomwan; Michael E Aziken (Wolters Kluwer Medknow Publications, 2021)
Background: As the number of older women attempting to conceive through donor oocyte-in vitro fertilization (DO-IVF) rises, their safety in pregnancy needs to be judiciously considered. Aims: This study aims to review the obstetric and perinatal outcomes of pregnancies achieved by DO-IVF. Study Setting and Design: A retrospective study design conducted at a private health facility with services for assisted reproduction and gynecologic endoscopy. Methods: A retrospective comparative study of all pregnancies achieved using DO-IVF and that using Self oocyte In-vitro fertilization (SO-IVF) treatment over a 3 years' period was performed. Statistical Analysis: Comparative analysis of demographic variables, major obstetric, and perinatal complications was done with Chi-square test and Student's t-test as appropriate. Regression analysis was done to determine a significant predictor variable for pregnancy and delivery outcome. The significance level was set at P < 0.05. Results: A total of 343 completed IVF treatment cycles was reviewed; there were 238 DO-IVF and 105 SO-IVF cycles, with clinical pregnancy rate of 41.6% and 37.1%, respectively. The DO-IVF group was significantly older than the SO-IVF group (46.1 years vs. 34.1 years, P < 0.001). Major obstetric complications identified, were hypertensive disorders in pregnancy (23.9%), preterm labor (16.7%), antepartum hemorrhage (11.6%). There was no statistically significant difference between the two groups in terms of obstetric complications and adverse maternal or perinatal outcomes. There were 97 (77.6%) singleton and 28 (22.4%) multiple pregnancies. Pregnancy complications were significantly associated with fetal plurality, P < 0.001. Multiple pregnancy had higher odds of experiencing adverse perinatal 4.96 (1.95-12.58) and maternal 7.16 (2.05-25.03) outcomes compared to singleton pregnancies, P < 0.001. Conclusion: Key obstetric outcomes did not differ between DO or SO IVF achieved pregnancy. Even for older women, satisfactory outcomes can be expected for pregnancies achieved by DO-IVF. It is, however, instructive that for multiple pregnancies, obstetricians should institute appropriate surveillance strategies during pregnancy and delivery period and also to develop institutional capacity for quality neonatal care.